Pemerolehan Bahasa Anak Usia 5 Tahun dengan Metode Penelitian Kualitatif Deskriptif: Analisis Komponen Fonologi, Morfologi, dan Sintaksis - Rosyida, Nurul Fauzani; Mustafiah, Imamatul; Rahayu April , Nita Dwi; Pulo Kelen, Redemptus; Aulia Hanif, Divanny; Fauziah, Muhardila (Indo-MathEdu Intellectuals Journal, 2024)
The aim of this research is to explore the acquisition process of five year old children using descriptive qualitative methodology. This research method is used to thoroughly describe how 5 year old children acquire knowledge, abilities and values in their development. This research collects data through observation, in-depth interviews, and analysis of relevant documents. This research involved children aged five years, their parents, and teachers who took formal or informal education. After that, the data collected was analyzed qualitatively by considering patterns, themes and contexts of children's learning. It is hoped that the results of this research will provide a complete picture of the acquisition process for five year old children. These findings may also provide parents, educators, and researchers with insight into the factors that influence five-year-olds' learning, so they can improve their teaching and support methods.